PENGARUH PROGRESSIVE MUSCLE RELAXATION TERHADAP TINGKAT KECEMASAN PRE OPERASI DI RUMAH SAKIT SANTA ELISABETH MEDAN TAHUN 2018 - Mardiati Barus; Murni Sari Dewi Simanullang; Erni Cahyani Putri Gea (Program Studi Ners UNIVERSITAS SARI MUTIARA INDONESIA, 2018)
Operation is in one of the medical action that needs mental and physical preparation. Medical action could cause physiology interference that is worries. Base on preliminary data, there are many patient get big worries before operation does. One of the interventions to reduce worries pre operation is progressive muscle relaxation.This research is aim to identify the different rates worry level before and after doing the progressive muscle relaxation to the patient pre operation in Santa Elisabeth Hospital Medan 2018.The research design is using Quasy Experimental by One Group PreTest Post Test without Control Group Design.The result of this research is about pre test 14,33 and post test 12,40 the significancy value p value = 0,000 that state there is correlation between progressive muscle relaxation to worries level in pre operation in Santa Elisabeth hospital 2018. The conclusion of this progressive muscle relaxation research is there is correlation between reduce worry to pre patient operation. Nurse is expected to do progressive muscle relaxation as one of intervention nursing to reduce worry to pre operation patient.